If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -6y + -12 = 0 Reorder the terms: -12 + -3x + -6y = 0 Solving -12 + -3x + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + -3x + 12 + -6y = 0 + 12 Reorder the terms: -12 + 12 + -3x + -6y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -3x + -6y = 0 + 12 -3x + -6y = 0 + 12 Combine like terms: 0 + 12 = 12 -3x + -6y = 12 Add '6y' to each side of the equation. -3x + -6y + 6y = 12 + 6y Combine like terms: -6y + 6y = 0 -3x + 0 = 12 + 6y -3x = 12 + 6y Divide each side by '-3'. x = -4 + -2y Simplifying x = -4 + -2y
| 18-1x=-7x+30 | | 2x+y=14-3x | | -3n(n^2+2n)= | | 4w+5w+1w= | | x(x+1)(x+2)(x+3)=360 | | 0.333y-0.5=0.1666y | | 4(2x-3)+1=9 | | 3.25=4.3r+16-r | | 2y-6=2x-6 | | ln(x)=.71 | | 6(x-6)+14=6x-21 | | 2(x+4)+2(x-2)=3x+12 | | 6y-8x=12 | | -8m-5m=13 | | 18x-4x=7 | | -4(x-10)=34 | | -3x+3=6x-9 | | 6.5?4x= | | -12a=36 | | 108=-6x+8(4x+7) | | -3(c-2)-4=5-(c-1) | | 4x+6-7x=-8 | | .89=5.3n+9.5 | | 6-4=16-9d | | -3x+72=107+-10x | | 3x^2-7x-29=0 | | X=-7y+21 | | 5x-2(2x-8)=5(2x-7)+7x | | 0.5n=0.4+0.2n | | X+0.3x=100.00 | | -4b+9-7= | | 4x+5=5x-10 |